Cultural Empowerment and Economic Upturn: Unveiling Bojonegoro's Wayang Thengul Tourism - Wintari Wintari; Dwiningtyas Padmaningrum; Haryani Saptaningtyas (Universitas Muhammadiyah Sidoarjo, 2023)
This research delves into the cultural and economic potential of Bojonegoro regency in East Java, focusing on the unique three-dimensional puppetry tradition known as Wayang Thengul. Situated in Kedungkrambil hamlet, Sumberjo Village, Margomulyo sub-district, this study employs qualitative descriptive methods including in-depth interviews, observation, and documentation to explore the empowerment of local communities through the development of cultural tourism. By harnessing the heritage of Wayang Thengul and leveraging geographical advantages, the project